Influence Mechanism of Energy Efficiency Label on Consumers’ Purchasing Behavior of Energy-Saving Household Appliances - Si-dai, Guo; Cheng-Peng, Lu; Hang, Li; Ning, Zhu (Frontiers in Psychology, 2021)
The implementation of mandatory energy efficiency labeling is an effective way to change consumers' consumption habits and guide them to buy energy-saving appliances. However, there are few studies on the impact of energy efficiency labels on consumers’ purchasing behavior. Based on the theory of planned behavior, social cognitive theory and signaling theory, this paper constructs a theoretical model of the effect of the energy labels on consumers’ purchasing behavior of energy-saving household appliances. The survey data of 396 household appliance consumers in Mianyang City, China, are collected by the interception method, and the theoretical model is tested by structural equation modeling (SEM). The empirical results show that consumers' cognition and perceived value of energy efficiency labels significantly affect label trust. Perceived value plays a significant role in consumers’ purchasing behavior of energy-saving appliances, while label cognition and label trust indirectly influence consumers' purchasing behavior through the intermediary variable of purchase intention. External environmental factors such as publicity and education as well as subjective norms affect consumers' actual purchasing behavior through the intermediary effect of purchase intention. This study provides important insights into the policy intervention measures to promote consumers' purchasing behavior of energy-saving appliances.